2013
DOI: 10.1177/1933719112473659
|View full text |Cite
|
Sign up to set email alerts
|

Protein Z Variants Associated With Protein Z Plasma Levels and With Risk of Idiopathic Recurrent Miscarriage

Abstract: Protein Z (PZ) deficiency due to anti-PZ autoantibodies and/or mutations in PZgene was linked with adverse pregnancy outcomes, including idiopathic recurrent miscarriage (IRM). We investigated the association of rs3024718, rs3024719, rs3024731, rs3024778, rs3024772, and rs3024735 (G79A) PZ variants and changes in PZ levels in 287 women with IRM, and 308 control women. Of the 6 single nucleotide polymorphisms (SNPs) analyzed, higher minor allele frequency of rs3024735 (G79A) and rs3024731 were seen in IRM cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 40 publications
0
14
1
Order By: Relevance
“…The study of Grandone et al (2004) has also reported that PZ deficiency is not linked with unexplained fetal loss, which is due to the small sample size, low plasma PZ cut-off values (1.43G0.76 mg/ml in healthy controls), and exclusion of women with known inherited (FV Leiden or FII G20210A mutations and protein C, protein S, or antithrombin deficiency) or acquired (antiphospholipid antibodies) thrombophilia. The above-mentioned studies involved lower numbers of subjects compared with the studies of Gris et al (2002Gris et al ( , 2003 and Sofi et al (2010), and our study (Sater et al 2011, AlShaikh et al 2013), indicating study under-power. Interestingly, both the Bretelle et al …”
Section: Pz In Pregnancy Complicationsmentioning
confidence: 84%
See 4 more Smart Citations
“…The study of Grandone et al (2004) has also reported that PZ deficiency is not linked with unexplained fetal loss, which is due to the small sample size, low plasma PZ cut-off values (1.43G0.76 mg/ml in healthy controls), and exclusion of women with known inherited (FV Leiden or FII G20210A mutations and protein C, protein S, or antithrombin deficiency) or acquired (antiphospholipid antibodies) thrombophilia. The above-mentioned studies involved lower numbers of subjects compared with the studies of Gris et al (2002Gris et al ( , 2003 and Sofi et al (2010), and our study (Sater et al 2011, AlShaikh et al 2013), indicating study under-power. Interestingly, both the Bretelle et al …”
Section: Pz In Pregnancy Complicationsmentioning
confidence: 84%
“…More recent studies, including a meta-analysis (Sofi et al 2010) and our case-control Bahraini study (AlShaikh et al 2013), have confirmed the strong relationship between low PZ levels and adverse pregnancy complications. The meta-analysis of Sofi et al (2010) involving 714 patients and 515 controls has demonstrated a strong association of PZ deficiency with pregnancy complications (OR (95% CI)Z3.42 (2.51-4.66)).…”
Section: Pz In Pregnancy Complicationsmentioning
confidence: 89%
See 3 more Smart Citations